2017
DOI: 10.3348/jksr.2017.76.4.294
|View full text |Cite
|
Sign up to set email alerts
|

Hemichorea-Hemiballismus Associated with Hyperglycemia: A Case Report

Abstract: This is an Open Access article distributed under the terms of the Creative Commons Attribution Non-Commercial License (http://creativecommons.org/licenses/by-nc/4.0) which permits unrestricted non-commercial use, distribution, and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
1
1
1
Order By: Relevance
“…Heo and Jeong in 2017 described a case of NKHH-induced hemichorea with T1 hyperintensities in the striatum, mesial temporal lobe, and cerebral peduncle, as well as FLAIR hyperintensities in the striatum and temporal lobe. 9 However, these abnormalities were not as extensive as those noted in this case. A case of NKHH-induced hemichorea reported by Uchibori et al in 2003 demonstrated striatal T1 hyperintensity with transient FLAIR hyperintensity and contrast enhancement in the ipsilateral temporal lobe.…”
Section: Discussioncontrasting
confidence: 50%
“…Heo and Jeong in 2017 described a case of NKHH-induced hemichorea with T1 hyperintensities in the striatum, mesial temporal lobe, and cerebral peduncle, as well as FLAIR hyperintensities in the striatum and temporal lobe. 9 However, these abnormalities were not as extensive as those noted in this case. A case of NKHH-induced hemichorea reported by Uchibori et al in 2003 demonstrated striatal T1 hyperintensity with transient FLAIR hyperintensity and contrast enhancement in the ipsilateral temporal lobe.…”
Section: Discussioncontrasting
confidence: 50%
“…Teori lain yang muncul baru-baru ini adalah mekanisme terjadinya perdarahan ptekial akibat rusaknya sawar darah otak yang diinduksi oleh hiperglikemia sehingga menyebabkan iskemia transien pada neuron striatal. 10,11 Mekanisme yang paling mungkin menyebabkan terjadinya defisit neurologis tersebut ialah hiperglikemia yang menyebabkan hiperosmolaritas dan penurunan kadar GABA dan berakibat iskemia fokal. Sebuah studi melaporkan bahwa pada kondisi hiperglikemia non-ketosis, siklus Krebs dihambat, metabolisme GABA meningkat hingga kadarnya menurun sehingga menurunkan ambang aktivitas kejang.…”
Section: Diskusiunclassified
“…includes both simple hyperglycemia and HHNS. HC-HB can be a symptom of NKH in primary diabetes mellitus with a classical CT neuroimaging finding of hyperattenuation over unilateral or bilateral of the putamen and/or caudate nucleus (Bhattarai 2016;Heo & Jeong 2017;Lai et al 1996;Oh et al 2002;Patni & Bagga 2017;Zaitout 2012). It is a rare condition with only 53 patients reported in the largest published case series between 1985 until 2001.…”
Section: Nkhmentioning
confidence: 99%